Muzolimine: a new high-ceiling diuretic suitable for patients with advanced renal disease. Issue 6264 (21st February 1981) - Dal Canton, A; Russo, D; Gallo, R; Conte, G; Andreucci, V E
Abstract : Muzolimine was administered by mouth to 24 patients with creatinine clearances ranging from 4 to 28 ml/min to treat oedema or hypertension, or both. In four of these 24 patients muzolimine was given after intravenous high-dose frusemide had been unsuccessful. Muzolimine significantly increased urine volume and excretions of sodium, chloride, and potassium ions. Its diuretic efficacy was further shown by a mean reduction in body-weight of 8% and by the disappearance of oedema in all affected patients, even those refractory to intravenous frusemide. No rebound phenomenon was observed after the drug was stopped. Mean blood pressure was reduced in all hypertensive patients. Blood pressure was restored to normal in five out of seven patients treated with muzolimine alone and 10 out of 11 in whom muzolimine had been added to previously unsatisfactory antihypertensive treatment. Muzolimine was well tolerated by all patients. Muzolimine appears to be the diuretic of choice when treating patients with advanced renal disease.